Gurumon gurumayum, a new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae) from Arunachal Pradesh, northeastern India - Pati, Sameer K. (European Journal of Taxonomy, 2022)
A new genus and new species of potamid crab, Gurumon gurumayum gen. et sp. nov., are described from the Arunachal Pradesh State of northeastern India. Gurumon gen. nov. has affinities with Abormon Mitra, Pati & Ng, 2021, Pararanguna Dai & Chen, 1985, and some species of Potamiscus Alcock, 1909, but the new genus can easily be differentiated from them mainly by its low external orbital angle, the relatively stouter exopod of the third maxilliped, and the relatively broader male pleonal somite 6. Their male first gonopods are also different from each other. Counting Gurumon gurumayum gen. et sp. nov., India is currently known for ten genera and 24 species of potamiscine freshwater crabs, and Arunachal Pradesh for eight genera and 11 species of these crabs. The current nomenclatural problems with Potamiscus are also discussed.